Livestock rabies in Para state, Brazil: a descriptive study (2004 to 2013) - Andrade, Elane A (Col?gio Brasileiro de Patologia Animal, 2020)
Rabies is an important zoonosis to public health associated with lethal encephalitis and economic losses. Analysis of its spatial distribution is a meaningful tool in understanding its dispersion, which may contribute to the control and prophylaxis of the disease. This study analyzed the spatial-temporal distribution of rabies outbreaks in livestock in Par? state, Brazil, from 2004 to 2013. We used records of neurological syndromes obtained from the state?s livestock authority (Adepar?). The analysis recorded 711 neurological syndromes reports in livestock, of which 32.8% were positive for rabies. In 8% of the neurological syndromes (n=57) was not possible to perform the analysis because of bad-packaging conditions of the samples sent. Outbreaks involved at least 1,179 animals and cattle were the most affected animal species (76.8%). The numbers of reported neurological syndromes and of rabies outbreak shad strong positive correlation and exhibited decreasing linear trend. Spatially, most outbreaks occurred in two mesoregions in Par? (Northeast and Southeast). One of the justifications for this spatial distribution may be related with the distribution of the animals in the state, since these mesoregions are the largest cattle producers in Par? and have most of their territory deforested for pasture implementation.